Lembah Elqui / Valle de Elqui / Elqui Valley - Ian Campbell (PORTAL: Journal of Multidisciplinary International Studies, 2017)
The three versions of Ian Campbell’s poem about Valle de Elqui (in Chile) presented here comprise a poem he first wrote in Spanish, then in English and finally in a more powerful version in Indonesian, which was published in 2012 in the literary pages of the Jakarta mass media daily Kompas. Campbell regards this whole process as emblematic of his explorations in trilingual poetics, namely what does a ‘concept’/poem idea look like if done in the three languages with which he has some degree of written knowledge or fluency: English, Spanish, Indonesian. This mirrors the ‘three-pronged’ title ‘Selatan-Sur-South’ that he adopted for the collection of his poetry in PORTAL vol. 5, no. 1, 2008. The Indonesian version, ‘Lembah Elqui, ‘was included in Campbell’s poetry and prose collection Tak ada Peringatan (Vivid Publishing, 2013). In each version now the reference is to Gabriela Mistral (1889-1957), Nobel Prize Laureate for Literature (1945), whose burial place lies in Monte Grande in the Valle de Elqui in northern Chile.